Poetry and Languid Charm, 2007: Swahili Music From Tanzania and Kenya - From the 1920s to the 1950s. Topic Records Ltd. - TSCD 936. Compiled by Janet Topp Fargion, Curator, World and Traditional Music Section, British Library Sound Archive. One compact disc. Booklet (15 pp.) with notes by Janet Topp Fargion and photographs. - McConnachie, Boudina (International Library of African Music, 2007)
pages: 132-134
Keywords: Poetry; African Music; Tanzania; Kenya; Swahili Music; Languid Charm